Ten years after the international committee of medical journal editors’ clinical trial registration initiative, one quarter of phase 3 pediatric epilepsy clinical trials still remain unpublished: a cross sectional analysis - Lampert, Anette; Hoffmann, Georg F.; Ries, Markus (PLOS ONE, 2016)
Introduction Although selective reporting of clinical trial results introduces bias into evidence based clinical decision making, publication bias in pediatric epilepsy is unknown today. Since there is a considerable ambiguity in the treatment of an important and common clinical problem, pediatric seizures, we assessed the public availability of results of phase 3 clinical trials that evaluated treatments of seizures in children and adolescents as a surrogate for the extent of publication bias in pediatric epilepsy. Methods We determined the proportion of published and unpublished study results of phase 3 clinical trials that were registered as completed on ClinicalTrials.gov. We searched ClinicalTrials.gov, PubMed, and Google Scholar for publications and contacted principal investigators or sponsors. The analysis was performed according to STROBE criteria. Results Considering studies that were completed before 2014 (N = 99), 75 (76%) pediatric phase 3 clinical trials were published but 24 (24%) remained unpublished. The unpublished studies concealed evidence from 4,437 patients. Mean time-to-publication was 25 SD ± 15.6 months, more than twice as long as mandated. Conclusion Ten years after the ICMJE’s clinical trials registration initiative there is still a considerable amount of selective reporting and delay of publication that potentially distorts the body of evidence in the treatment of pediatric seizures.